A Content Analysis of Published Articles in Montenegrin Journal of Sports Science and Medicine from 2019 to 2020 - Marija Bubanja; Marina Vukotic; Ivan Vasiljevic (Journal of Anthropology of Sport and Physical Education)
Montenegrin magazine for sports science and medicine “Montenegrin Journal of Sports Science and Medicine” (MJSSM), is the only magazine in Montenegro with the index in two world databases: Web of Science and Scopus. Articles published in this magazine stem from different fields of sports science: biomechanics, physiology, sports medicine, anthropology, methodology and other fields related to sports. In the previous three editions of this magazine, 30 articles have been published which are classified according to the following science fields: Sports Medicine, Sports Training, Anthropology of Sport; Sports Psychology; Sports Physiology; Systematic Analysis of Sports Articles. The analysis revealed that the articles in the field of Sports Training are the most numerous, therefore the most cited works as well as the best positioned. Sports Training is an integral part of a triage technology which enables an athlete’s transformation processes of certain segments of the anthropological status as well as an improvement of technical and tactical elements which ultimately lead to the realization of the top sports achievements. Also, results published in the magazine “Montenegrin Journal of Sports Science and Medicine” in the field of Sports training could be beneficial in monitoring athletes, notifying corrections during training methods, estimating and improving capability differences among athletes from different sports orientations.